Sociologi och samhälleliga värderingar. En självbiografisk illustration (Sociologisk Forskning, 1997)
Sociology and social values. an autobiographical illustrationThis paper gives a self-biographical illustration of how prevailing ideas and social structures have influenced the directions, presumptions and interpretations of the author’s research and research-results during the post-war period with its radical social changes. The science-, planning- and development-optimistic ideas of the late 1940’s and 1950’s made the author inclined towards a positivistic kind of sociology. The radical critical ideas of the 1960’s and 1970’s influenced the author towards a socialistic optimistic type of sociology focusing on welfare reforms, equality and democracy. The crisis period of the 1980s and 1990s made the author sceptical towards ”fundamentalistic” sociology, characterized by too many presumptions and evaluations. The age of uncertainty requires the invention of a more careful and sensitive critical sociology and new forms of politics beyond the Left and Right that can cope with today’s social problems concerning environmental destruction, global market-processes and global economic crises, ethnic and gender conflicts and the crises of the national welfare state.